Answer:
A
Step-by-step explanation:
To sovle this we must combine the numbers togther and the variables togther.
We have:
8c+6-3c-2
Lets take out the c's and combine them:
8c -3c
=
5c
Now lets take out the numbers:
6-2
=
4
Now lets put these back together and we get the expression:
5c+4
This looks like A.
Hope this helps! :D
Answer:
Step-by-step explanation:
100-10 : 100
90 : 100
504 : x
x=540x100/90
x=50400/90
x=560
For the first one it is x=1 the second one X=8
Answer:
9 cm.
Step-by-step explanation:
Let the height of the pyramid be h cm, then the height of the cuboid is (15 - h) cm.
Volume of the pyramid:
= 1/3 * h * s^2 where s is the length of a side of the square base.
= hs^2/3 cm^3
Volume of the cuboid:
= s^2(15 - h).
So we have:
hs^2/ 3 = 300.......................(1)
s^2(15 - h) = 600..................(2)
From equation (1) :
h s^2 = 900
s^2 = 900/h
Now substitute for s^2 in equation (2) :
(900/h)(15 - h) = 600
Multiply through by h:
900(15 - h) = 600h
13500 - 900h = 600h
1500h = 13500
h = 9 cm (answer). brainliest?
Answer: 15 i think
Step-by-step explanation: